THE TOPONYMY OF THE VILLAGE OF PADESH, BLAGOEVGRAD AREA – SEMANTIC CLASSIFICATION AND STRUCTURAL SPECIFICS - Nadelina Ivova (Езиков свят)
The present text describes the toponymy of the village of Padesh, Blagoevgrad area. It represents a semantic classification of the place names and observes their structural specifics. The text also mentions some word-formation and morphological peculiarities. More than 210 microtoponyms and oykonyms are classified in three main groups. The first group analyses toponyms derived from geographical characteristics or from some other specifics of the place. The group contains 98 names and the analysis shows that 47 of them include geographical terms. The second group observes toponyms reflected by cultural history of Padesh - names related to the village agriculture and forestry, religious concepts and settlement structure. The most of the toponyms are classified as a possessives in the third group. The least of them are formed by а personal name, а nickname or by an adjective. The other ones are names for ownership, derived by proper names and some specific suffixes such as -ица and -ец. The most of the toponyms in that group come from resident/ family names or have as a constituent a possessive adjective. All the names are analyzed as simple toponyms, complex toponyms and compounds. The text finds that the toponymy of the village of Padesh contains mostly simple place names, less often the toponyms formed by an adjective and a noun and just two of the place names are compounds.